2016
DOI: 10.1177/1028315316662976
|View full text |Cite
|
Sign up to set email alerts
|

The Role of International Service-Learning in Facilitating Undergraduate Students’ Self-Exploration

Abstract: This paper examines the role of international service learning (ISL) in facilitating undergraduate students' exploration of their conception of self-the use of specific values and beliefs to define one's role in society and relationships with others. ISL is intentionally structured activities involving students in social services for community members in overseas settings. Existing research underscores the importance of inducting students to other-oriented (showing care and empathy for others) values in facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…20 Yang et al indicated that service-learning impacts students' conceptions of self as leaders who promote and uphold long-term benefits for community members and their peers. 21 They further argue that international service-learning has the potential for supporting students' self-exploration by giving them opportunities to incorporate moral, cultural, and leadership values into their conceptions of self.…”
Section: Service-learning Program: Peril or Promise?mentioning
confidence: 99%
“…20 Yang et al indicated that service-learning impacts students' conceptions of self as leaders who promote and uphold long-term benefits for community members and their peers. 21 They further argue that international service-learning has the potential for supporting students' self-exploration by giving them opportunities to incorporate moral, cultural, and leadership values into their conceptions of self.…”
Section: Service-learning Program: Peril or Promise?mentioning
confidence: 99%
“…The Pyramid Model (Osland, 2018) provides a useful five-level structure to conceptualize these universal global leadership characteristics: 1) global knowledge; 2) threshold traits of integrity, humility, inquisitiveness and self-resilience; 3) attitudes and orientations (the global mindset) toward a global context; 4) interpersonal skills for working cross-culturally in teams; and 5) systems thinking skills. These competencies are evident among the students who have participated in short term study abroad trip, specifically in areas such as intercultural competency (Jackson, 2015;Cushner and Chang, 2015;Elola and Oskoz, 2008), emotional intelligence (Holtbrugge and Engelhard, 2016), moral and ethical reasoning (Luo and Jamieson-Drake, 2015), altruism and ability to appreciate cultural differences (Yang et al, 2016), perception of self and worldview in relation to culturally diverse others (Bell, Gibson, Tarrant, Perry III, and Stoner, L. (2016) and global citizenship awareness (Coers, Rodriguez, Roberts, Emerson, and Barrick, 2012). Pless, Maak, and Stahl (2011) summarized learning for business students in terms of responsible mind-set, ethical literacy, cultural intelligence, global mindset, self-development, and community building.…”
Section: Benefits Of Study Abroad In Areas Of Global Competencymentioning
confidence: 99%
“…The prior preparation education included cultural competency training, communication and coordination with community, and comprehensive assessment and strategic planning for S-L activities [7]. This course facilitate the students to reflect on their conceptions of self [8]. This self-exploration included reflecting on the culture and knowledge on their own country, Korea.…”
Section: Prior Activitiesmentioning
confidence: 99%